REY and Trace Element Chemistry of Fluorite from Post-Variscan Hydrothermal Veins in Paleozoic Units of the North German Basin - Nadoll, Patrick; Rehm, Meike; Duschl, Florian; Klemd, Reiner; Kraemer, Dennis; Sosnicka, Marta (Geosciences, 2018)
Hydrothermal fluorites from Paleozoic sedimentary rocks and volcanic units in the North German Basin (NGB) have been investigated to create a petrographic and geochemical inventory—with particular focus on strategic elements such as rare earth elements (REE)—and to uncover possible links between the post-Variscan hydrothermal mineralization in the NGB and bordering areas such as the Harz Mountains and Flechtingen Calvörde Block (FCB). Fluorites from ten localities underwent a detailed petrographic examination, including SEM-BSE/CL imagery, and were compositionally analysed using LA-ICP-MS. Overall, REY concentrations are comparatively low in fluorite from all investigated areas—the median sum of REY ranges from 0.3 to 176 ppm. EuropiumCN anomalies are slightly negative or absent, indicating that either the formation fluid experienced temperatures above 250 °C or that fluid-rock interactions and REE enrichment was likely controlled by the source rock (i.e., volcanic) composition and complexation processes. Fluorites from the Altmark-Brandenburg Basin (ABB) and the Lower Saxony Basin (LSB) display distinctly different REYCN signatures, suggesting that fluid compositions and genetic processes such as fluid-rock interaction differed significantly between the two areas. Complex growth zones and REYCN signatures in fluorite from the ABB and the FCB reflect geochemical variability due to adsorption processes and intrinsic crystallographic controls and imply that they are genetically related. Two petrographically and geochemically distinct generations are observed: Fluorite I—light SEM shades, relatively enriched in LREE; Fluorite II—darker SEM shades, comparatively depleted LREE, slightly higher HREE concentrations. These fluorite generations represent zoned (or cyclical) growth within a single progressive hydrothermal event and do not reflect a secondary remobilization process. We demonstrate that increasing Tb/La ratios and decreasing La/Ho ratios can be the result of continuous zoned growth during a single mineralizing event, with significant compositional variations on a micron-scale. This has implications for the interpretation of such trends and hence the inferred genetic evolution of fluorite that displays such geochemical patterns. The complex micro-scale intergrowth of these generations stresses the need for detailed petrographic investigations when geochemical data are collected and interpreted for mineral exploration.<br
Keywords: Remobilization; Trace elements; North German Basin; Rare earth elements; Zoned growth; Hydrothermal veins; Fluorite